2014
DOI: 10.1160/th13-10-0832
|View full text |Cite
|
Sign up to set email alerts
|

Peri-interventional endothelin-A receptor blockade improves long-term outcome in patients with ST-elevation acute myocardial infarction

Abstract: Endothelin (ET)-1 is a pro-fibrotic vasoconstrictive peptide causing microvascular dysfunction and cardiac remodelling after acute ST-elevation myocardial infarction (STEMI). It acts via two distinct receptors, ET-A and ET-B, and is involved in inflammation and atherogenesis. Patients with posterior-wall STEMI were randomly assigned to intravenous BQ-123 at 400 nmol/minute (min) or placebo over 60 min, starting immediately prior to primary percutaneous coronary intervention (n=54). Peripheral blood samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 49 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…ET-1 induces proinflammatory mechanisms, superoxide anion production, cytokine secretion [29, 30], endoplasmic reticulum stress [31], and synthesis of cell adhesion molecules, such as soluble ICAM-1 [28]. Several studies have suggested a potential interaction between the ET and the immune systems in the pathogenesis of pulmonary hypertension [29], portal hypertension [32, 33], preeclampsia (elevated blood pressure in pregnancy) [34, 35], and myocardial infarction [36]. For example, TNF-α is an important stimulus for ET-1 in response to placental ischemia during preeclampsia [34].…”
Section: Role Of Et-1 In the Cardiovascular And Renal Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…ET-1 induces proinflammatory mechanisms, superoxide anion production, cytokine secretion [29, 30], endoplasmic reticulum stress [31], and synthesis of cell adhesion molecules, such as soluble ICAM-1 [28]. Several studies have suggested a potential interaction between the ET and the immune systems in the pathogenesis of pulmonary hypertension [29], portal hypertension [32, 33], preeclampsia (elevated blood pressure in pregnancy) [34, 35], and myocardial infarction [36]. For example, TNF-α is an important stimulus for ET-1 in response to placental ischemia during preeclampsia [34].…”
Section: Role Of Et-1 In the Cardiovascular And Renal Systemsmentioning
confidence: 99%
“…In addition, chronic exposure to activated CD4(+) T cells in response to placental ischemia results in ET-1 activation as a mechanism to increase blood pressure during pregnancy [35]. In myocardial infarction patients, BQ-123 leads to reduction in plasma myeloperoxidase (MPO), a marker of neutrophil activation [36]. …”
Section: Role Of Et-1 In the Cardiovascular And Renal Systemsmentioning
confidence: 99%